The consuming fire - Scalzi, John, 1969- (Scalzi, John, 1969- Interdependency, 2018)
"The second, thrilling novel in the bestselling Interdependency series, from Hugo Award-winning author John Scalzi. The Interdependency, humanity's interstellar empire, is on the verge of collapse. The Flow, the extra-dimensional conduit that makes travel between the stars possible, is disappearing, leaving entire star systems stranded. When it goes, human civilization may go with it--unless desperate measures can be taken. Emperox Grayland II, the leader of the Interdependency, is ready to take those measures to help ensure the survival of billions. But nothing is ever that easy. Arrayed before her are those who believe the collapse of the Flow is a myth--or at the very least, an opportunity that can allow them to ascend to power. While Grayland prepares for disaster, others are preparing for a civil war, a war that will take place in the halls of power, the markets of business, and the altars of worship as much as it will take place between spaceships and battlefields. The Emperox and her allies are smart and resourceful, but so are her enemies. Nothing about this power struggle will be simple or easy... and all of humanity will be caught in its widening gyre" --